IMPLEMENTASI PROGRAM RT KEREN DALAM PERSPEKTIF HUKUM KELUARGA ISLAM: IMPLIKASI TERHADAP TERWUJUDNYA KELUARGA SAKINAH DI KOTA BLITAR - Robiah Nuzul Inayah; Fina Wardani; Aisyatul Azizah; Fahmi Mustika Ramadhani; Siti Khodijah Nurul Aula (USRAH: Jurnal Hukum Keluarga Islam, 2026)
This article analyzes the implementation of the RT Keren Program from the perspective of Islamic family law and its implications for the realization of sakinah families in Blitar City. The RT Keren Program is a local government innovation that promotes community participation based on the Rukun Tetangga (RT) in strengthening the social, economic, and spiritual resilience of families. This study aims to analyze how the implementation of this program affects the achievement of sakinah families for the community in Blitar City. This study uses a qualitative descriptive method, based on Edward's implementation theory and the indicators of sakinah families according to Yusuf Al-Qardawi. The results show that the RT Keren program has been implemented well but is not yet running optimally. This study emphasizes the integration between decentralization policies and the concept of sakinah families from an Islamic law perspective, which shows that the RT Keren program has a positive impact on the achievement of sakinah families at the local level. These findings recommend that the RT Keren model be used as a national prototype for strengthening Islamic value-based family welfare policies.